Hamstring versus peroneus longus autograft for arthroscopic anterior cruciate ligament reconstruction – which is better for Indian population? - Muddapu, Pardhasaradhi; Tadi, Shipra; Sattaru, Kishore B.; Korada, Ravi K. (International Journal of Research in Medical Sciences, 2025)
Background: Hamstring autograft has been a popular option for anterior cruciate ligament (ACL) reconstruction. Of late, the use of peroneus longus tendon has shown promising results. Indian population is predominantly kneeling population where squatting and sitting crossed are associated with daily living activities. This study involves the comparative analysis of the morbidities associated with both the grafts and the choice of autograft based on the Indian population needs. Methods: A comparative cohort study was conducted on 60 patients who underwent ACL reconstruction during 2022-2023.The patients were randomly assigned for either peroneus longus or hamstring autograft. After a follow-up of one year, the donor site morbidities were assessed using Lysholm score for knee and foot and ankle disability index (FADI) for ankle joint. Results: A significant statistical difference (p value ≤0.001) was seen in the mean time required to harvest hamstring and peroneal grafts. Although the Lysholm scores were statistically insignificant (p=0.03) in both the groups, 20% of patients with hamstring graft, recorded VAS pain score >7/10 while deep squatting and loading heavy weights. FADI scores of the donor side and contralateral side in patients with peroneal graft showed statistically insignificant results (p value=0.06). Conclusions: Owing to the graft diameter, robust quality, tensile strength and lesser knee joint morbidity, peroneus longus can be considered as a better alternative autograft to the Indian population. However, in athletes, a careful decision should be made as further long-term studies are required to assess the ankle joint morbidity due to this autograft.